Evaluating hydroponics and aquaponics: Comparative insights into sustainability and strawberry quality - Korbee-Peinado, Nathalie; Bautista-Bueno, Begoña; García-Sánchez, Marta; Cobos-Mateo, Pablo; Ferres García, José Luis; López-Figueroa, Félix; Medrano, Evangelina (Elsevier, 2025)
Aquaponics provides a more sustainable alternative to hydroponics by integrating fish farming with plant cultivation, thereby reducing the need for chemical fertilizers and promoting the natural recycling of nutrient waste. This study compared the cultivation of 'Primoris' strawberry plants in two systems: a traditional hydroponic system using agricultural fertilizers and an aquaponic system utilizing effluents from thick-lipped grey mullet (Chelon labrosus) fishponds. Despite the significantly lower concentrations of key nutrients (primarily nitrate and phosphate) in the aquaponic system, total yield exceeded 600 g per plant, with no significant differences between the two cultivation methods. Strawberry leaves from the aquaponic system exhibited higher levels of chlorophyll (Chl a: 1.7 ± 0.15 mg·g⁻¹ FW, Chl b: 0.98 ± 0.09 mg·g⁻¹ FW), carotenoids (1.2 ± 0.09 mg·g⁻¹ FW), and calcium (1.3 %). No differences were observed in photosynthesis, organic carbon, total nitrogen, or organic matter content in the leaves between the two systems. Additionally, anthocyanin content in aquaponically grown strawberries was higher (23.5 ± 4.3 mg PE·100 g−1 FW). Fruit quality parameters (including °Brix, acidity, vitamin C, and firmness) were comparable between the two cultivation systems, as confirmed by a blind sensory test. These findings suggest that aquaponic strawberry cultivation can reduce fertilizer usage without compromising yield, fruit quality, or plant health. This highlights aquaponics as a viable and more sustainable alternative to conventional agriculture, including hydroponic methods.
Keywords: Fresas - Mejora genética; Hidropónica; Aquaponic; Fruit quality; Hydroponic; Nutrient recycling; Strawberry cultivation; Sustainability